Adverse left ventricular remodeling by glycoprotein nonmetastatic melanoma protein B in myocardial infarction. Issue 2 (25th October 2016) - Järve, Anne; Mühlstedt, Silke; Qadri, Fatimunnisa; Nickl, Bernadette; Schulz, Herbert; Hübner, Norbert; Özcelik, Cemil; Bader, Michael
ABSTRACT: Cardiac diseases are the leading cause of death. Available treatment approaches are not sufficient to reverse persistent cardiac damage after injury; thus, the search for new therapeutic targets is essential. Our microarray‐based screening in rat hearts 24 h after myocardial infarction (MI) yielded glycoprotein nonmetastatic melanoma protein B (GPNMB), which is known to be involved in inflammation and fibrosis after tissue injury. However, its role in the heart was elusive. We found increased cardiac expression levels of GPNMB in rats and mice after MI. Analysis of DBA/2J mice, which lack functional GPNMB due to a spontaneous point mutation, showed that systemic GPNMB deficiency was associated with preserved cardiac function and less left ventricular dilation after MI compared with DBA/2J mice with reconstituted GPNMB expression. These improvements were associated with decreased expression of matrix metalloproteinase 9, the cardiac stress genes for natriuretic peptides (atrial natriuretic peptide and brain natriuretic peptide), and β‐myosin heavy chain after MI. Moreover, GPNMB deficiency attenuated the dilated cardiomyopathy in muscle lim protein knockout mice but could not prevent cardiac hypertrophy induced by isoprenaline infusion. This is the first experimental study to show that GPNMB adversely influences myocardial remodeling.—Jühlstedt, S., Qadri, F., Nickl, B., Schulz, H., HÖzcelik, C., Bader, M. Adverse left ventricular remodeling by glycoprotein nonmetastatic melanoma protein B in myocardial infarction. FASEB J. 31, 556–568 (2017). www.fasebj.org